Evaluasi Program Aksi Desa Mandiri Pangan di Kabupaten Bantul - Zuchainah, Siti; Apriliyanti, Indri (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2010)
Food security is one of the main pillars of developing resilient and sustainable economic development. Food security itself refers to the availability of food and ones access to it. Food autonomy at the household level, requires special attention as it forms the foundation of food autonomy of food at the national level. Food Autonomy Action Programme , is one of government interventions tailored toward achieving national economic resilient and security. The program targets directly the poor as they often experience food insecurity. The objective in overcoming food insecurity in Bantul district. The study specifically examined and identified factors which contribute to the effectiveness of the program implementation. The research used descriptive qualitative methods. The location of the research was was in two villages., Muntuk Village Dligo Sub-District and Selopamioro Village Imogiri Sub-district, which were categorized as food insecure that. Findings showed that the implementation of the Food Autonomy Action Programme in Bantul district has been effective. This is reflected by an analysis of both output indicators the implementation of program proved relevant to target population as well as outcome decrease in food insecurity of the population relative to the level of food at the society level.